Monogenic Inborn Errors of Immunity with impaired IgG response to polysaccharide antigens but normal IgG levels and normal IgG response to protein antigens - Fasshauer, Maria; Dinges, Sarah; Staudacher, Olga; Völler, Mirjam; Stittrich, Anna; von Bernuth, Horst; Wahn, Volker; Krüger, Renate (Frontiers in Pediatrics, 2024)
In patients with severe and recurrent infections, minimal diagnostic workup to test for Inborn Errors of Immunity (IEI) includes a full blood count, IgG, IgA and IgM. Vaccine antibodies against tetanus toxoid are also frequently measured, whereas testing for anti-polysaccharide IgG antibodies and IgG subclasses is not routinely performed by primary care physicians. This basic approach may cause a significant delay in diagnosing monogenic IEI that can present with an impaired IgG response to polysaccharide antigens with or without IgG subclass deficiency at an early stage. Our article reviews genetically defined IEI, that may initially present with an impaired IgG response to polysaccharide antigens, but normal or only slightly decreased IgG levels and normal responses to protein or conjugate vaccine antigens. We summarize clinical, genetic, and immunological findings characteristic for these IEI. This review may help clinicians to identify patients that require extended immunologic and genetic evaluations despite unremarkable basic immunologic findings. We recommend the inclusion of anti-polysaccharide IgG antibodies as part of the initial routine work-up for possible IEI.